Harmony in Diversity at Poltekpar Bali: Implementation the First Principle of Pancasila - Ni Desak Made Santi Diwyarthi; I Wayan Adi Pratama (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Religious diversity in Indonesia represents both a strength and a challenge in fostering national unity, particularly in the context of higher education. As the world's largest archipelagic nation with six officially recognized religions, Indonesia upholds Pancasila as its foundational philosophy, with the first principle being "Belief in One Supreme God." This study investigates the role of student religious organizations at Politeknik Pariwisata Bali (Poltekpar Bali) in reinforcing this principle while simultaneously promoting interfaith harmony and inclusivity among students from various faith backgrounds. Employing a qualitative research methodology, this study utilizes literature review and participatory observation to examine the contributions of student-led religious organizations, including Rohkristo (Christian and Catholic students), KAMHD (Hindu students), IKLIM (Muslim students), and KMB (Buddhist students). Findings indicate that these organizations not only serve as spaces for spiritual growth and religious expression but also play a significant role in fostering cross-cultural understanding through a variety of collaborative initiatives. These include interfaith dialogues, joint community service projects, disaster relief efforts, environmental campaigns, and shared celebrations of religious holidays. Such activities cultivate an atmosphere of respect, empathy, and peaceful coexistence among students of different beliefs. By engaging in constructive interreligious engagement, student religious organizations at Poltekpar Bali contribute meaningfully to the embodiment of Pancasila values in a pluralistic educational environment. This study underscores the importance of empowering student-led religious communities as key actors in promoting social cohesion, interfaith solidarity, and the ethical development of future tourism professionals in Indonesia's multicultural society.